The Dictionary of Cell and Molecular Biology - Lackie, J. M (Elsevier, 2007)
The over 10,000 entries in this comprehensive Dictionary of Cell and Molecular Biology provide clear and concise definitions for anyone working in life sciences today. It incorporates related terms from neuroscience, genetics, microbiology, immunology, pathology, and physiology. This fourth revised edition reflects the enormous changes brought about by the explosion of new technologies, especially high throughput approaches and functional genomics. As a result, this edition is over 30% larger than the previous edition, with 3400 new entries. As with the prior edition, additions are reflective.